Determinasi Ketimpangan Pendapatan di Indonesia: Peran Pendidikan, Zakat, dan Korupsi - Cupian, Cupian; Hakim, Ahmad Luqman; Hardiawan, Donny; Rayyan, Ramadhansyah; Prinary, Verina Araminda (Jurnal Riset Ilmu Ekonomi, 2025)
This study examines the influence of Zakat, Infaq, and Alms (ZIS), corruption, and education on income inequality in Indonesia. Utilizing a quantitative approach with time-series data from 2011 to 2022, the research employs the Autoregressive Distributed Lag (ARDL) framework to analyze both long-term and short-term dynamics. Findings indicate that ZIS and corruption exert a negative and significant impact on income inequality, whereas education shows a positive but insignificant effect. The study concludes that religious philanthropy and institutional integrity are pivotal in narrowing the economic gap. Policy implications suggest that the government should optimize zakat management systems and intensify anti-corruption measures to ensure more equitable income distribution. Additionally, strategic improvements in educational quality are essential to support sustainable and long-term economic equality.